Study on the impact and attention of cover papers for PLOS journals: Evidence from propensity score matching - Xiaoqing Chen; Li Liu; Weichao Li; Meiyuan Xing; Xiuyang Li (PLoS ONE, 2025)
Background Studies on the impact and attention of cover papers within open-access journals from the same publisher remain lacking. The objective of this study was to explore the effect of being featured as a cover paper on the impact and attention of papers for PLOS journals using propensity score matching (PSM). Methods Cover and non-cover papers published in five PLOS journals (i,e., PLOS Biology, PLOS Computational Biology, PLOS Genetics, PLOS Pathogens, PLOS Neglected Tropical Diseases) between 2008 and 2017 were selected. Three scientometric indicators, citations (as scholarly impact indicator), and Altmetric attention score (AAS) and Mendeley readers (as social and academic attention indicators) of each paper were collected from altmetric.com. Two datasets were obtained via 1:2 propensity score matching: one spanning 2008–2017 for analyzing citations and reader counts, and another covering 2011–2017 for AAS analysis. Then, the Wilcoxon signed-rank test, univariate analysis, and multivariate linear regression analysis were conducted to explore the impact and attention of cover papers versus non-cover papers. Results Among 24,080 papers, 1,760 were successfully matched for analysis of citation frequency and readership, and 1,212 were successfully matched for Altmetric attention analysis. After PSM, cover papers exhibited significantly higher citations (v = 560, P < 0.001), much more readers (v = 528, P < 0.001), and higher AAS (v = 1384, P < 0.001) than non-cover papers. Further multivariate regression analysis of the PSM-adjusted data revealed significant associations, with regression coefficients of 0.145 for citations, 0.174 for readership, and 0.691 for AAS (P < 0.05). Conclusions The findings of this study suggested that being featured on the cover was statistically positively associated with an article’s academic impact and public visibility, especially in terms of the societal attention. However, the relationship was weak.